Pathologic Findings in the Hearts of Patients with Acquired Immunodeficiency Syndrome - Klima, Marcella (1991)
To determine the extent of myocardial involvement in acquired immunodeficiency syndrome, we reviewed specimens of cardiac tissue obtained during autopsies of 54 patients with this disease. Forty-nine of the specimens showed subtle microscopic changes, the most common being lymphocytic infiltration (49 cases), unevenness of myocardial fibers (34 cases), interstitial fibrosis (28 cases), and myocardial atrophy (22 cases). Twenty-one of the specimens showed a morphologic abnormality that may be classified as a mild cardiomyopathy. Four had microscopic evidence of lymphocytic myocarditis; clinically, however, such myocarditis was diagnosed in only 1 patient, who died of cardiac failure. In a retrospective review, 7 additional hearts (among the 54) showed mild, nonspecific cardiac changes. The causative mechanism and significance of AIDS-related cardiac involvement remain uncertain; nevertheless, physicians should be aware of such involvement, to avoid overburdening the heart with medications that would further impair the myocardium. (Texas Heart Institute Journal 1991;18:116-21)